STRATEGI PENELITIAN DAN PEMANFAATAN DATA KUBUR BAGI STUDI WILAYAH DI BALI - Fadhila Arifin Aziz (BRIN, 2000)
Bali, until now, is known for its rich values and unique culture. The process of forming culture in several areas of Bali has differences and diversity from the Pleistocene to the Holocene period through the process of contact with communities from outside Bali. By applying a more systematic framework of thought, the results of archaeological research that are oriented to the region and the Bali region are expected to contribute to the study of the archipelago's culture. The above contributions can be in the form of information on ideological ideas as well as physical forms from the past that are still visible until now.